The genus Camelina (Cruciferae) in Mongolia and China reviewed on the basis of herbarium materials from the Institute of General and Experimental Biology of the ASM (UBA) and the Komarov Botanical Institute (LE) - V. I. Dorofeyev; U. Enkhmaa (Труды по прикладной ботанике, генетике и селекции, 2020)
Herbarium collections of the genus Camelina preserved at the Institute of General and Experimental Biology of the Academy of Sciences of Mongolia (UBA) and the Komarov Botanical Institute of the Russian Academy of Sciences (LE) were studied. The collections of these Herbaria contain materials of 3 species from Mongolia (C. caucasica (Sinsk.) Vass., C. sativa (L.) Crantz, C. sylvestris Wallr.) and 4 from China (C. sativa, C. linicola Schimp. et Spenn., C. microcarpa Andrz., C. sylvestris).